Dietary Intervention With α-Amylase Inhibitor in White Kidney Beans Added Yogurt Modulated Gut Microbiota to Adjust Blood Glucose in Mice - Wang, Shenli; Guo, Chongye; Xing, Zhikai; Li, Meng; Yang, Haiying; Zhang, Yunting; Ren, Fazheng; Chen, Lishui; Mi, Shuangli (Frontiers in Nutrition, 2021)
White kidney beans contain α-amylase inhibitors can be used in diet for weight reduction. In this study, we investigated the potential of white kidney bean (phaseolus vulgaris L.) extract enriched in α-amylase inhibitor as a food additive in yogurt to regulate blood glucose in hyperglycemic animals. Five groups of C57BL/6J mice were fed for eight weeks with standard chow diets, high-fat diets (HFD) or high-fat diets with supplement of α-amylase inhibitor in white kidney beans (P. vulgaris extract, PVE), yogurt (Y) and PVE added yogurt (YPVE) respectively. The HFD weakened glucose tolerance and caused insulin resistance in mice, and changed the characteristics of intestinal flora. The intervention of Y, PVE and YPVE decreased blood glucose, insulin, hyperlipidemia and inflammatory cytokine levels in mice fed with HFD. Moreover, the YPVE could regulate the components of host intestinal microbiota toward a healthy pattern, significantly increased the metabolic-related flora Corynebacterium, Granulicatella and Streptococcus, while decreased Paraprevotella and Allobaculum. Thus, YPVE markedly increased functions of “Amino Acid Metabolism”, “Energy Metabolism”, “Nucleotide Metabolism” and declined functions of “Glycan Biosynthesis and Metabolism”. Consequently, YPVE could be developed as a new functional food because of its beneficial prebiotic properties in the metabolic syndrome.